O MODELO DE ASSISTÊNCIA MÉDICA DE PEDRO ERNESTO (1932): ALGUMAS CONSIDERAÇÕES (Revista de História Regional, 2007)
This article analyses the medical assistance model stablished in the capital of Brasil during Pedro Ernesto's administration (1931-1935). In order to achieve that we will reflect an upon the decree n.4.252, proclaimed in July 8 th, 1932. We are particulary interested in identifying what kind of interference this decree could promote in the medical occupation organization in the constitution of the medical profession as so as in keeping its autonomy. We also tried to understand the reasons why specialised literature did not give almost any attenti-on to the role that Pedro Ernesto's medical assistance model had in the History of Brazil's Medical Care.